PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA DI PERUMDA TIRTA HIDAYAH KOTA BENGKULU - Rahmadan, Syahru; Onsardi, Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research aims to determine the influence of human resource development and work motivation on work productivity in Perumda Tirta Hidayah, Bengkulu City, both partially and simultaneously. There are several independent variables (x) that will be discussed in this research, including Human Resource Development and Work Motivation. The objects of this research are the employees of Perumda Tirta Hidayah, totaling 120 respondents. In this research, several data analysis techniques were used, including using instrument tests, classical assumption tests, analysis of respondent responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of the multiple linear regression test, the regression equation obtained is as follows: Y = 3.070 + 0.487 (X1) + 1.103 (X2). Based on the multiple linear regression equation, it can be interpreted that: Constant value 3.070 means that if the HR Development (X1) and Work Motivation (X2) variables are equal to zero, then the Work Productivity variable (Y) is constant. The Regression Coefficient The Regression Coefficient X2 (Work Motivation) of 1.103 means that if Work Motivation increases by one unit, the Work Productivity value will increase. Assuming that the Work Motivation variable (X2) is considered fixed or constant. From the results of the tests that have been carried out, it can be concluded that the HR Development and Work Motivation variables have a partial or simultaneous effect on work productivity among employees of Perumda Tirta Hidayah, Bengkulu City. Keywords: The Influence of Human Resource Developmen, Motivation, Productivity